Iron chelators for the treatment of cancer - Yu, Yu; Gutierrez, E.; Kovacevic, Z.; Saletta, F.; Obeidy, P.; Rahmanto, Y.; Richardson, D. (Bentham Science Publishers, 2012)
The study of iron chelators as anti-tumor agents is still in its infancy. Iron is important for cellular proliferation and this is demonstrated by observations that iron-depletion results in cell cycle arrest and also apoptosis. In addition, many iron chelators are known to inhibit ribonucleotide reductase, the iron-containing enzyme that is the rate-limiting step for DNA synthesis. Desferrioxamine is a well known chelator used for the treatment of iron-overload disease, but it has also been shown to possess anti-cancer activity. Another class of chelators, namely the thiosemicarbazones, have been shown to possess anti-cancer activity since the 1950's, although their mechanism(s) of action have only recently been more comprehensively elucidated. In fact, the redox activity of thiosemicarbazone iron complexes is thought to be important in mediating their potent cytotoxicity. Moreover, unlike typical iron chelators which simply act to deplete tumors of iron, several thiosemicarbazones (i.e., Bp44mT and Dp44mT) do not induce this effect, their anti-cancer efficacy being due to other mechanisms e.g., redox activity. Other reports have also shown that some thiosemicarbazones inhibit topoisomerase IIa, demonstrating that this class of agents have multiple molecular targets and act by various mechanisms. The most well characterized thiosemicarbazone iron chelator in terms of its assessment in humans is 3-aminopyridine-2-carboxaldehyde thiosemicarbazone (3-AP). Observations from these clinical trials highlight the less than optimal activity of this ligand and several side effects related to its use, including myelo-suppression, hypoxia and methemoglobinemia. The mechanisms responsible for these latter effects must be elucidated and the design of the ligand altered to minimize these problems and increase efficacy. This review discusses the development of chelators as unique agents for cancer treatment.